Parental risk attitudes and children's secondary school track choice - Guido Heineck; Oliver Wölfel (Institute for the Study of Labor (IZA), 2010)
It is well known that individuals' risk attitudes are related to behavioral outcomes such as smoking, portfolio decisions, and also educational attainment, but there is barely any evidence on whether parental risk attitudes affect the educational attainment of dependent children. We add to this literature and examine children's secondary school track choice in Germany where tracking occurs at age ten and has a strong binding character. Our results indicate no consistent patterns for paternal risk preferences but a strong negative impact of maternal risk aversion on children's enrollment in upper secondary school.
Keywords: I21; J24; 330; educational choice; risk attitudes; SOEP; Eltern; Risikopräferenz; Kinder; Bildungsverhalten; Weiterführende Schule; Schätzung; Deutschland